2003
DOI: 10.1148/radiol.2273020303
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Left Ventricular Function with Interactive Real-Time Spiral and Radial MR Imaging

Abstract: An interactive real-time spiral gradient-echo and an interactive real-time radial steady-state free precession sequence were investigated for the quantitative assessment of left ventricular function. Data were acquired in 18 patients without electrocardiographic triggering and breath holding. With the interactive real-time spiral gradient-echo sequence, significant underestimation of endocardial and epicardial volumes was demonstrated; with the interactive real-time radial steady-state free precession sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Thus, the observed EDV differences are not exaggerated, but rather attenuated by the poorer spatial resolution in sequence protocol C. k-space sampling may play a role, too. Spuentrup et al (27) showed a good agreement for radial interactive real-time SSFP sequences, whereas spiral interactive real-time cine acquisitions significantly underestimated EDV, ESV, and SV. The implementation of parallel acquisition techniques in sequence 1 appears to be a promising alternative to reduce acquisition time for cine MR ventriculometry instead of using the shared phases approach.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the observed EDV differences are not exaggerated, but rather attenuated by the poorer spatial resolution in sequence protocol C. k-space sampling may play a role, too. Spuentrup et al (27) showed a good agreement for radial interactive real-time SSFP sequences, whereas spiral interactive real-time cine acquisitions significantly underestimated EDV, ESV, and SV. The implementation of parallel acquisition techniques in sequence 1 appears to be a promising alternative to reduce acquisition time for cine MR ventriculometry instead of using the shared phases approach.…”
Section: Discussionmentioning
confidence: 96%
“…Real-time cine frames can also be acquired during free breathing and without ECG-gating. This is a major advantage enabling cardiac MR imaging examinations in patients with arrhythmia or in patients who are unable to hold their breath (23,27,28). The time savings of the real-time technique are tremendous as only one breath-hold period is needed to cover the entire LV compared to about 12 minutes with the conventional single-slice approach (29).…”
Section: Discussionmentioning
confidence: 99%
“…As atrial clot formation is commonly associated with atrial fibrillation, further sequence modifications may be required to obtain sufficient image quality in all cases. One solution may include real-time MR or other k-space sampling strategies (such as radial acquisitions) as these are less sensitive to motion artifacts [56][57][58][59]. Recently, several fibrin-specific contrast agents have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The beginning of this century coincided with the reintroduction and revival of the balanced steady-state free-precession GE sequence, which rapidly became the preferred bright-blood sequence for dynamic cardiac imaging (cine MRI) (Barkhausen et al 2001;Carr et al 2001;Thiele et al 2001;Plein et al 2001;Moon et al 2002;Lee et al 2002;Fieno et al 2002;Alfakih et al 2003a;Hori et al 2003;Spuentrup et al 2003). Use of this sequence, introduced in the early 1980s, was hampered for a long time because of issues such as main field nonuniformity, eddy currents, and inhomogeneous magnetic susceptibility, which have been solved with the newest-generation scanners.…”
Section: Mri Sequence Designmentioning
confidence: 99%
“…This has urged several groups to develop clinically useful ultrafast and real-time sequences with an acceptable temporal resolution (below 50 ms) and in-plane spatial resolution (below 2.5 mm) (Kramer et al 2008). In addition to use of techniques such as view or echo sharing and parallel imaging, a substantial reduction in measurement time can be achieved by developing novel strategies to fill the k-space (e.g., partial k-space filling, radial or spiral k-space filling), and by exploiting correlations in k-space and time (k-t) such as k-t BLAST and k-t SENSE techniques (see ''Cardiac MR Physics''; Setser et al 2000;Nagel et al 2000;Kaji et al 2001;Barkhausen et al 2002;Lee et al 2002;Spuentrup et al 2003;Hori et al 2003;Kühl et al 2004;Taylor et al 2005;Jahnke et al 2006Jahnke et al , 2007Muthurangu et al 2008;Lurz et al 2009). …”
Section: Ultrafast and Real-time Cine Imagingmentioning
confidence: 99%